2011
DOI: 10.4236/fns.2011.24050
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Solid State NMR to Evaluate the Carbohydrates in Commercial Coffee Granules

Abstract: Coffee brings many health benefits due to its chemical constituents. Based on this information, it is essential to know the main chemical compounds from coffee granules; the intermolecular interaction among the coffees compounds and the molecular components homogeneity. In this study six types of roasted commercial coffee were evaluated by solid state nuclear magnetic resonance (NMR), employing carbon-13 (<sup>13</sup>C) and hydrogen (<sup>1</sup>H) nucleus. Carbon-13 was analyzed apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…As shown in the Supporting Information, the chemical shift in the FA–PEG spectrum at 29.60 ppm probably corresponds to the chemical shift at 29.91 ppm in the GO–FA spectrum, and the chemical shift in the FA–PEG spectrum at 36.84 ppm possibly corresponds to the chemical shift at 37.26 ppm in the GO–FA spectrum. In Figure B, the intense peak at 70.05 ppm is in the region of N/O alkyl chemical shifts and originated from the CH 2 O and CH 2 NH 2 /CH 2 NH structures of PEG. ,, The chemical shifts corresponding to the C-substituted aromatic carbons occur in the region 110–140 ppm, while those for O- and N-substituted aromatic carbons occur between 140 and 160 ppm. Therefore, we can conclude that the chemical shifts at 151.17 and 155.12 ppm are due to the N-substituted aromatic carbons from the FA moieties. , The chemical shift at 172.80 ppm was attributed to both the carbon in the amide group of the FA structure and the bond formed between FA–PEG and GO. These chemical shifts demonstrate that the employed functionalization method was efficient to bond FA–PEG to GO.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…As shown in the Supporting Information, the chemical shift in the FA–PEG spectrum at 29.60 ppm probably corresponds to the chemical shift at 29.91 ppm in the GO–FA spectrum, and the chemical shift in the FA–PEG spectrum at 36.84 ppm possibly corresponds to the chemical shift at 37.26 ppm in the GO–FA spectrum. In Figure B, the intense peak at 70.05 ppm is in the region of N/O alkyl chemical shifts and originated from the CH 2 O and CH 2 NH 2 /CH 2 NH structures of PEG. ,, The chemical shifts corresponding to the C-substituted aromatic carbons occur in the region 110–140 ppm, while those for O- and N-substituted aromatic carbons occur between 140 and 160 ppm. Therefore, we can conclude that the chemical shifts at 151.17 and 155.12 ppm are due to the N-substituted aromatic carbons from the FA moieties. , The chemical shift at 172.80 ppm was attributed to both the carbon in the amide group of the FA structure and the bond formed between FA–PEG and GO. These chemical shifts demonstrate that the employed functionalization method was efficient to bond FA–PEG to GO.…”
Section: Resultsmentioning
confidence: 86%
“…The chemical shifts observed in the CP/MAS 13 C NMR spectra can be divided into four characteristic chemical shift regions, assigned to alkyl C (0–45 ppm), O/N alkyl C (45–110 ppm), aromatic C (110–160 ppm), and carboxyl/carbonyl C (160–220 ppm). In the GO–FA spectrum, the chemical shift at 29.91 ppm was attributed to the CH 2 alkyl group of FA and CH 2 alkyl groups of PEG, and the chemical shift at 37.26 ppm was attributed to the other CH 2 alkyl group of FA (Figure B). This attribution is based in the FA spectrum given in the literature and the FA and FA–PEG CP/MAS 13 C NMR spectra (Figure S9). As shown in the Supporting Information, the chemical shift in the FA–PEG spectrum at 29.60 ppm probably corresponds to the chemical shift at 29.91 ppm in the GO–FA spectrum, and the chemical shift in the FA–PEG spectrum at 36.84 ppm possibly corresponds to the chemical shift at 37.26 ppm in the GO–FA spectrum.…”
Section: Resultsmentioning
confidence: 95%
“…There were two wide bands at 30–50 ppm and 120–135 ppm for KL spectrum. Research ,, showed that these two bands can be attributed to CH 2 carbons and CH carbons, respectively. When processing the KL spectrum using the CPNQS methodology that suppresses the CH 2 /CH band, the spectrum became similar to that of 190 °C MRL.…”
Section: Resultsmentioning
confidence: 99%
“…CP and INEPT can be used in solid state NMR analysis to study the rigid and the mobile part of a food respectively and thus provide various types of information. For example, this approach was applied to study the mobile components of granule coffee, such as triglycerides and the rigid domains, such as carbohydrates (Nogueira et al., ).…”
Section: Fundamentals Of Nmr Spectroscopy‐relevance To Food Sciencementioning
confidence: 99%